Efficient heat spreader using supersonically sprayed graphene and silver nanowire. (25th January 2020) - Kim, Tae-Gun; Park, Chan-Woo; Woo, Deok-Yoon; Choi, Jeehoon; Yoon, Sam S.
Highlights: Supersonically sprayed rGO-AgNW dissipates heat to remediate a line hotspot. The effect of film thickness is investigated to identify the optimal thickness of the film. The addition of AgNW reduce the overall film thermal resistance. Abstract: Hotspots in high-power and high-density microelectronic devices are a major problem because insufficient thermal dissipation can cause device malfunction. We introduce supersonically sprayed thin films made of reduced graphene oxide (rGO) and silver nanowires (AgNW) that can efficiently dissipate heat to remediate hotspots. Film deposition by cold supersonic spraying provides superior adhesion and requires no post-deposition treatment, making it compatible with a wide range of surface materials. A rGO film heat spreader is deposited on an Al2 O3 substrate (10 × 10 cm 2 ), which is Joule-heated using a nickel–chrome wire. Heat quickly dissipates over the entire surface due to the rGO film, eliminating the localized hotspot. The effect of film thickness is investigated to identify the optimal thickness of the deposited rGO film heat spreader. The cooling capability of pure graphene oxide films is characterized and compared to the heat dissipation performance of a hybrid rGO–AgNW film and an uncoated substrate. The morphology and surface properties of the films are characterized using scanning electron microscopy, Raman spectroscopy, optical profilometry, and thermal infrared imaging. An rGO film thickness of 10 μm produced the lowest thermal resistance and the addition of AgNW enhanced film thermal performance by reducing the thermal resistance.